Refinements of the Lower Bounds of the Jensen Functional - Iva Franjić; Sadia Khalid; Josip Pečarić (Abstract and Applied Analysis)
The lower bounds of the functional defined as the difference of the right-hand and the left-hand side of the Jensen inequality are studied. Refinements of some previously known results are given by applying results from the theory of majorization. Furthermore, some interesting special cases are considered.